2022
DOI: 10.3390/app122111154
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of Wearable Technologies: A Comparative Analysis of Textile-Based and Accessory-Based Wearable Products

Abstract: Wearable technology components have been integrated into accessories and then clothes over the evolutionary process. In the future, it is predicted that wearable technologies will be patchable and implantable. Despite progress in wearable technologies, there is an adaptation problem in wearable technologies. One of the most important reasons for this problem is the negative product experiences of the users. In this study, we investigated the user experiences of accessory-based and textile-based wearable techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The proposed methodology establishes a systematic framework for conducting usability studies for wearable devices thereby supporting research in the direction of usability, user experience and human-centricity of wearable devices. Baskan and Goncu-Berk (2022) studied the user experiences associated with the usage of two distinct types of wearable devices including accessory based and textile based devices. The data for user experience study was acquired through surveys and the findings suggested the preference for textile based alternative as compared to the counterpart on the basis of user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed methodology establishes a systematic framework for conducting usability studies for wearable devices thereby supporting research in the direction of usability, user experience and human-centricity of wearable devices. Baskan and Goncu-Berk (2022) studied the user experiences associated with the usage of two distinct types of wearable devices including accessory based and textile based devices. The data for user experience study was acquired through surveys and the findings suggested the preference for textile based alternative as compared to the counterpart on the basis of user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The five attributes to consider for measuring the overall user experience of the inertial motion capture suit, namely, 1) Discomfort, 2) Burden, 3) Distraction, 4) Flexibility issue, and 5) Emotion were shortlisted after a comprehensive literature search on the user experience aspects for wearable devices in various domains such as sports, ergonomics, rehabilitation and animation industry (Baskan and Goncu-Berk, 2022;Knight and Baber, 2005;Pearson, 2009). Participants were provided with the following explanations of these attributes and corresponding Likert scale descriptors.…”
Section: User Experience Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…As two key factors, intelligence and comfort in wearable products have become a research hotspot in this field. 1 Among them, the flexible pressure sensor can collect the signals of human physiological parameters in real-time according to different needs, and plays a complementary role in monitoring human activities and health status; [2][3][4][5] Portable heating wearable products can improve wearing comfort. 6,7 Flexible sensors can be divided into three types: piezoresistive, 8 piezoelectric, 9 and capacitive.…”
Section: Introductionmentioning
confidence: 99%
“…Functional textiles allow the incorporation of biosensors and other electronic devices, which elevates their preventive potential. However, research shows that end users do not use wearable devices due to unfamiliarity with their premise and design interface, and a lack of short-term results [ 11 , 12 , 13 ]. Thus, usability evaluations from laboratory prototypes using user-centered design can be promising in device development and potential usefulness, ease of use and learning, and user satisfaction [ 9 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%